2019
DOI: 10.1186/s13148-019-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

The hyper-activation of transcriptional enhancers in breast cancer

Abstract: BackgroundActivation of transcription enhancers, especially super-enhancers, is one of the critical epigenetic features of tumorigenesis. However, very few studies have systematically identified the enhancers specific in cancer tissues.MethodsHere, we studied the change of histone modifications in MMTV-PyVT breast cancer model, combining mass spectrometry-based proteomics and ChIP-seq-based epigenomics approaches. Some of the proteomic results were confirmed with western blotting and IHC staining. An inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…Our data on SEs bound by the AR expand on the role of SEs recently shown for other cancer types, in some cases allowing for stratification predictive of treatment response (Cejas et al, 2019;Gelato et al, 2018;Zhang et al, 2016). Interestingly, in breast cancer, estrogen receptor-bound SEs are also bound by MED1 and FOXA1, which act as facilitators for the interaction with neighboring enhancers (Bojcsuk et al, 2017), and lists of highly active SEs which potentially play a critical role in this tumor type have just been reported (Hazan et al, 2019;Li et al, 2019). Another important recent finding is that oncogenic SEs are inclined to undergo double-strand breaks and are therefore highly vulnerable to deficiencies in cellular DNA repair mechanisms.…”
Section: Resultssupporting
confidence: 76%
“…Our data on SEs bound by the AR expand on the role of SEs recently shown for other cancer types, in some cases allowing for stratification predictive of treatment response (Cejas et al, 2019;Gelato et al, 2018;Zhang et al, 2016). Interestingly, in breast cancer, estrogen receptor-bound SEs are also bound by MED1 and FOXA1, which act as facilitators for the interaction with neighboring enhancers (Bojcsuk et al, 2017), and lists of highly active SEs which potentially play a critical role in this tumor type have just been reported (Hazan et al, 2019;Li et al, 2019). Another important recent finding is that oncogenic SEs are inclined to undergo double-strand breaks and are therefore highly vulnerable to deficiencies in cellular DNA repair mechanisms.…”
Section: Resultssupporting
confidence: 76%
“…Lower levels of H4K5 and H4K8 acetylation are seen in 4C, 4C11−, and 4C11+ in comparison to melan-a cells. In parallel, the H4K12ac and H4K16ac changed across the multiple pairwise comparisons correlated with poor patient outcomes [68] and the decrease in H3K23me1 was also verified in breast cancer when compared to normal tissues [69].…”
Section: Discussionmentioning
confidence: 86%
“…H3K9me2 levels were also found to be increased in melanoma compared to normal skin tissue [ 66 ] whereas H3K27me3 levels were lower in metastatic versus primary melanoma cases [ 67 ]. In parallel, low H3K18ac levels in cancer were already correlated with poor patient outcomes [ 68 ] and the decrease in H3K23me1 was also verified in breast cancer when compared to normal tissues [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that about 31% (201/645) of tumor-altered H3K4me3 regions, which do not overlap with TSSs (‘altered.noTSS’ promoters), may represent a subclass of enhancers in tumor samples. GeneHancer was recently introduced as a comprehensive database of human enhancers and their inferred target genes [ 47 ]. GeneHancer revealed that 152/201 (>75%) of ‘altered.noTSS’ promoters intersected with enhancers and then predicted the corresponding targeted genes ( Table S12 ).…”
Section: Resultsmentioning
confidence: 99%